1988
DOI: 10.1093/oxfordjournals.aje.a115084
|View full text |Cite
|
Sign up to set email alerts
|

A Shigellosis Outbreak Traced to Commercially Distributed Shredded Lettuce

Abstract: In the period August 30-October 7, 1986, 347 persons in adjacent west Texas counties (Ector and Midland) contracted culture-confirmed Shigella sonnei gastroenteritis. A case-control study showed an increased risk of acquiring shigellosis in Ector County with eating at outlets of fast-food Restaurant A, and in Midland County with eating at Restaurant B or C. A second case-control study, of persons who had eaten at Ector County outlets of Restaurant A, showed an increased risk of acquiring shigellosis with eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 3 publications
0
44
0
1
Order By: Relevance
“…Shigella can grow rapidly in food ingredients held at ambient temperature [21,22] and S. sonnei has been shown to multiply in shredded lettuce and lettuce extract under certain conditions [13]. A wide range of salads have previously been involved in foodborne outbreaks of shigellosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shigella can grow rapidly in food ingredients held at ambient temperature [21,22] and S. sonnei has been shown to multiply in shredded lettuce and lettuce extract under certain conditions [13]. A wide range of salads have previously been involved in foodborne outbreaks of shigellosis.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of shigellosis have been associated with crowded conditions and poor personal hygiene, such as in prisons, daycare centers, schools and psychiatric institutions [5][6][7][8][9]. Large-scale outbreaks of foodborne shigellosis have been caused by infected food handlers practicing poor standards of personal hygiene [10][11][12][13]. Information on predominant sources and transmission routes of infections is crucial for targeted prevention of foodborne illnesses, and outbreaks frequently offer the only arena for gaining knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Risk assessment approach for fresh fruits Shigella spp. Kapperud et al 1995;Martin et al 1986;Saddik et al 1985;Davis et al 1988;Tauxe et al 1997;Fredlund et al 1987 Yersinia enterocolitica, Yersinia pseudotuberculosis Catteau et al 1985;Darbas et al 1985a,b;Gola et al 1990;Johannessen et al 2002;Salamah 1993;Tassinari et al 1994;Cavazzini et al 1982Cavazzini et al , 1989Nuorti et al 2004 Escherichia coli (EHEC, Besser et al 1993;Zepeda et al 1995;Odumeru et al 1997;Parish 1997;Tauxe et al 1997;Beuchat 1996;Cavazzini et al 1989;Bell and Kyriakides 1998;Franco et al 1987;…”
Section: Hazard Profilesmentioning
confidence: 99%
“…Good practice includes adequate training as well as both hand washing and toilet facilities which are further considered in Section 12.1.5. The contamination of shredded lettuce with Shigella by a food handler, caused a widespread outbreak in the US (Davis et al, 1988) and illustrates this possibility, although nothing similar has been reported for Salmonella or Norovirus and leafy greens. However, since the excretion of Norovirus by ill persons can be very high (EFSA Panel on Biological Hazards (BIOHAZ), 2012) this represents a risk factor for contamination.…”
Section: Worker Health and Hygiene Worker Trainingmentioning
confidence: 90%